On β-dual of vector-valued sequence spaces of Maddox - Suthep Suantai; Winate Sanhan (International Journal of Mathematics and Mathematical Sciences)
The β-dual of a vector-valued sequence space is defined and studied. We show that if an X-valued sequence space E is a BK-space having AK property, then the dual space of E and its β-dual are isometrically isomorphic. We also give characterizations of β-dual of vector-valued sequence spaces of Maddox ℓ(X,p), ℓ∞(X,p), c0(X,p), and c(X,p).